Ocean acidification as a hyperobject: mediating acidic milieus in the Anthropocene - Batalla, Oriol (Ecozon@: European Journal of Literature, Culture and Environment, 2023)
Through the usage of Timothy Morton’s hyperobjects (2013) as a heuristic, this essay aims to portray how Ocean Acidification can be read as a hyperobject affecting tropical seawaters and beyond. Furthermore, it illustrates how the arts and humanities, through their hermeneutical gaze, might help us grasp Ocean Acidification as a hyperobject and the wide array of other objects that act upon each other in such acidic oceanic waters. In this task, the article will close-read the “Underwater Woman” set of pictures by Christine Ren (2018) understanding the interpretation of art as a tool to reconnect cognition and emotion to move from the understanding of a crisis to the feeling of such crisis. Finally, it aims to shed light upon the implications arising from considering Ocean Acidification as a hyperobject. By connecting the theoretical, visual and political in the same narrative, this essay highlights the transformative potential of interpretation and thinking through hyperobjects. With this, the challenges of the Anthropocene are put at the forefront, situating specific events and problematics in a planetary scale. A través de la teoría de los Hiperobjetos de Timothy Morton (2013) como herramienta de análisis, este ensayo trata de ilustrar cómo la acidificación oceánica se ha convertido en un hiperobjeto, afectando las aguas más allá de los trópicos. Con esto en consideración, el ensayo busca analizar la manera en la cual las artes y las humanidades, a través de su mirada hermenéutica, pueden ayudarnos a comprender estos hiperobjetos junto con los diferentes objetos que actúan sobre ellos mismos en un entorno ácido. En esta tarea, analiza el set de fotografías Underwater Woman de Christine Ren (2018), comprendiendo la interpretación del arte como una herramienta para reconectar cognición con emoción, moviendo el sujeto des de la comprensión hasta la experiencia sensorial de la actual crisis. Finalmente, el artículo trata, de manera muy ambiciosa, de arrojar luz sobre las implicaciones que tiene discernir la ...